Sistem Informasi Pembelajaran Interaktif Mata Pelajaran Simulasi Digital Pada SMK Revany Indra Putra - Mulyadi Rusli; Teuku Djauhari; Fattachul Huda Aminuddin (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
The development of information and communication technology also influences the progress of learning media innovation, this study uses the information system development method consisting of three stages of research development procedures, namely needs analysis, design, development and implementation. The subjects of this study were students on digital simulation subjects majoring in computer network engineering at SMK Revany Indra Putra. The results showed that interactive learning media on digital simulation subjects could be a variety of media for learning. It is expected that the results of the development of this virtual module will have an impact on increasing students' mastery in learning digital simulations.